FLEXIBLE AND STRETCHABLE ELECTRONICS materials, design, and devices. - Li, Run-Wei. ([Place of publication not identified] PAN STANFORD Publishing, 2019)
With the recently well developed areas of Internet of Thing, consumer wearable gadgets and artificial intelligence, flexible and stretchable electronic devices have spurred great amount of interest from both the global scientific and industrial communities. As an emerging technology, flexible and stretchable electronics requires the scale-span fabrication of devices involving nano-features, microstructures and macroscopic large area manufacturing. The key factor behind covers the organic, inorganic and nano materials that exhibit completely different mechanical and electrical properties, as well as the accurate interfacial control between these components. Based on the fusion of chemistry, physics, biology, materials science and information technology, this review volume will try to offer a timely and comprehensive overview on the flexible and stretchable electronic materials and devices. The book will cover the working principle, materials selection, device fabrication and applications of electronic components of transistors, solar cells, memories, sensors, supercapacitors, circuits and etc.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Magnetism; SCIENCE / Life Sciences / General; TECHNOLOGY / Electronics / Microelectronics; Wearable technology; Flexible electronics